Evaluation of Different Extractants and Profile Distribution of Boron in Guava Orchard in an Inceptisol of Bihar - Mandal, Jajati; Padbhushan, Rajeev; Kumar, Sunil; Vimal, Binod Kumar; Das, Anupam; Bhowmick, Ritabrata; Kumar, Amarjeet (International Journal of Bio-resource and Stress Management, 2023)
The complex behavior of boron (B) in plant and soil systems makes it difficult to develop a suitable soil B extraction method that can determine the available nutrient status relative to plant needs under a wide range of soil conditions for various plant species. A suitable method for boron analysis must embrace the soil properties that determine the availability of Boron and acquiescent to routine laboratory analysis. On the basis of above premise three extractants, hot calcium chloride (CaCl2), Potassium dihydrogen Phosphate (KH2PO4) and dilute Hydrochloric acid (HCl) solutions were evaluated against the soils of Guava orchard. Soil samples were collected from three Guava orchards blocks at three different depths (0−15, 15−30 and 30−45 cm) and analyzed. The order of extracted B by the three extractants were KH2PO4>hot CaCl2>HCl. The amount of Boron extracted by each of the three extractants showed a gradual decrease with increase in depth. The amounts of B extracted by three extractants were also significantly correlated with each other; hot CaCl2↔KH2PO4 (r=0.561**), KH2PO4↔HCl, (r=0.484**) and HCl↔hot CaCl2, (r=0.642**). This shows dynamic equilibrium among the amount of B extracted by the extractants, indicating pools of extracted B in soils. The leaf samples from each tree were also collected and analyzed. B content of leaf tissue increased with increase in available B content in soil. Hot CaCl2 extracted B is more correlated with leaf B content in comparison to other extractants in different soil layer.